Generalized lichen nitidus in a child treated with topical corticosteroid. - Can, B.; Turkoglu, Z.; Kavala, M.; Zindanci, I.; Zemheri, E.; Sudogan, S. (European Journal of Pediatric Dermatology, 2010)
Lichen nitidus is an uncommon dermatosis with an unknown etiology. The generalized form of lichen nitidus is rare in childhood. We report here a 6-year-old boy who had multiple, flesh-colored, 1 to 3 mm papules on his face, trunk, elbows and abdomen. The patient was successfully treated with topical corticosteroid for 2.5 weeks.